Ações coletivas e ambiente empreendedor: uma análise do município de Maripá no Oeste do Paraná - Wendt, Eloisa (2018)
Currently, the market demands from companies a strategic position based on the preparation of the structure and the managers of the business. In agribusiness it is challenging to have small farms keep farmers in the field with financial security. Income diversification has been an option to overcome these challenges, as well as collective work among producers who have common objectives. However, there are many challenges, such as the demands on the entrepreneurial characteristics of each organization. In Maripá, in western Paraná, where the main productive activity is focused on agribusiness, rural properties added traditional soybean and corn crops to the production of other items such as broilers, pigs, fish and orchids. This research proposed to analyze the place, and pointed out that, for these activities, there are associative forms that work with rural producers, and this fact, motivated to understand the implications of collective actions for the formation and development of local entrepreneurship. The study was initially based on theories of entrepreneurship and collective action, and interviews and documentary research were also carried out at the site. The results showed that there is a collective culture among the inhabitants, since, in the studied environments, the activities of associations of rural producers have important representativeness, mainly the Maripá Aquiculture Association (Aquimap), Maripá Association of Orchid Farmers (AOM) and the C.Vale Agroindustrial Cooperative. The results pointed to the fact that these groups really are a form of strategy, since they mainly promote research and innovation. On the other hand, it also showed that there was a decisive participation of institutions, like Emater, and also of the municipal public power. In order for development to be presented in this way, it was necessary to apply efforts in the technification, in the improvement of the rural producers so that they could manage efficiently the properties and in innovation, to guarantee the competitiveness. The results also showed that the current state of development of the place would hardly be the same if there was no use of collective work. This study is significant because it analyzes the results of investing in associations in one place, specifically in the agricultural sector, which is the most representative in the western region of Paraná.